Optical properties, energy band gap and the charge carriers' effective masses of the R3c BiFeO3 magnetoelectric compound. (September 2020) - Lima, A.F.
Abstract: Calculations based on collinear and non-collinear spin density functional theory (DFT) were used to investigate the complex dielectric function spectrum, energy band gap, electronic band structure and the effective mass of the charge carriers of the R3c BiFeO3 magnetoelectric compound. Exchange and correlation electronic effects were taken into account using the local spin density approximation (LSDA), including the effective Hubbard (Ueff ) correction (LSDA + Ueff ). With Ueff = 6.0 eV and using the non-collinear spin DFT, the calculated complex dielectric function spectrum agrees very well with the experimental data from the literature. The optical absorption edge is estimated to be 2.2 eV, which according to the calculated electronic band structure corresponds to an indirect energy band gap. The electronic band structures also revealed that the aforementioned material has a direct band gap of 2.6 eV, which agrees with some experimental predictions. In addition, the hole and electron effective masses of the R3c BiFeO3 compound were computed. The smallest hole effective mass eigenvalue (0.38 m0 ) agrees with previous DFT calculations (0.67 m0 ). However, the smallest electron effective mass eigenvalue (0.39 m0 ) was one order of magnitude smaller than that reported in an earlier study (3.06 m0 ). Highlights: R3c BiFeO3 magnetoelectric compound was studied using non-collinear spin DFT + U. Effects of the collinear and non-collinear spin DFT + U were analyzed. Complex dielectric function spectrum agrees with experimental results. R3c BiFeO3 compound presents an indirect energy gap of 2.2 eV. Hole and electron effective mass eigenvalues of the R3c BiFeO3 were computed.